2012
DOI: 10.1149/1.3701976
|View full text |Cite
|
Sign up to set email alerts
|

Bridge to Fuel Cell Molecular Catalysis: 3D Non-Platinum Group Metal Catalyst in MEAs

Abstract: Transition metal porphyrin complexes have been mounted in a three dimensional homogenous distribution inside the ionomer of catalyst layers in MEAs to achieve competitive fuel cell catalysis activity. The effect of electrode components including ionomer, carbon, catalyst, and mediator, and ionomer film thickness, is investigated in fuel cell molecular catalysis system. Membrane electrode assembly (MEA) durability testing has been conducted. SEM and TEM techniques are employed to investigate molecular catalysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Recently, a series of papers has been published, in which a biomimetic approach has been applied to the creation of organometallic complexes used for oxygen reduction reaction (ORR) in a FC membrane electrode assembly (MEA). The aqua complex Ni II Ru II , [Ni II LRu II (H 2 O)(η 6 ‐C 6 Me 6 )](NO 3 ) 2 has been used as a catalyst for both HOR and ORR ([1](NO 3 ) 2 , where L= N , N ′‐dimethyl‐ N , N ′‐bis(2‐mercaptoethyl)‐1,3‐propanediol‐amine); and the MEA has been tested directly in the fuel cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a series of papers has been published, in which a biomimetic approach has been applied to the creation of organometallic complexes used for oxygen reduction reaction (ORR) in a FC membrane electrode assembly (MEA). The aqua complex Ni II Ru II , [Ni II LRu II (H 2 O)(η 6 ‐C 6 Me 6 )](NO 3 ) 2 has been used as a catalyst for both HOR and ORR ([1](NO 3 ) 2 , where L= N , N ′‐dimethyl‐ N , N ′‐bis(2‐mercaptoethyl)‐1,3‐propanediol‐amine); and the MEA has been tested directly in the fuel cell.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,aseries of papersh as been published, [6][7][8][9] in which ab iomimetic approachh as been applied to the creation of organometallic complexes used for oxygenr eduction reaction (ORR) in aF Cm embranee lectrode assembly (MEA).T he aqua complex Ni II Ru II ,[ Ni II LRu II (H 2 O)(h 6 -C 6 Me 6 )](NO 3 ) 2 has been used [7] as ac atalyst for both HOR and ORR ( [1](NO 3 ) 2 ,w here L = N,N'-dimethyl-N,N'-bis(2mercaptoethyl)-1,3-propanediol-amine);a nd the MEA has been tested directly in the fuel cell. Theo pen-circuit voltage (OCV) was 0.29 Va nd the maximum power density was 11 mWcm À2 .T hen, the authors have shown that the useo f peroxoc omplex [Ni II Ru IV ]l eads to an increase in the performanceo ft he FCs.T he OCV was increased to 0.42 V, and the power density reached the value of 26 mWcm À2 .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] In this framework, we expect the kinetic behavior of the film to be jointly governed by the catalytic reaction and the substrate diffusion inside the film as represented in Fig. It includes the case where charge transport proceeds through rapid electron hopping.…”
Section: Introductionmentioning
confidence: 99%
“…With these advances, the site density can be increased to levels that support high current densities. One approach is to build a 3D, molecular polymer redox layer on the electrode surfaces 5. The polymer redox layer includes a molecular catalyst, and this structure results in full access to all species (electrons, protons, and substrates) with increased reaction rates.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer redox layer includes a molecular catalyst, and this structure results in full access to all species (electrons, protons, and substrates) with increased reaction rates. In our previous studies,1, 5, 6 we proposed a polymer redox film having a non‐noble‐metal complex impregnated with Nafion as a new cathode catalyst layer for PEMFCs. In particular, a non‐noble‐metal catalyst (metal porphyrins) binds with the sulfonic acid sites of Nafion to form a 3D molecular catalyst, and the polymer redox film is attached to the electrode surface.…”
Section: Introductionmentioning
confidence: 99%